Images of the gender role in two ILO projects (Genava : International Lobour Organisation, 1992)
This booklet and video are guides for exploring the rules of women in development, for inspiring discussion and for expanding women's participation in technical co-operation projects today and in the future
Copy available in DVD format
Editor, Henrik Lindemann ; music, Pierre Dorge
Narrator: Vivienne Mckee
Keywords: Identity (Psychology); Self-perception